Hardness of Cooked Milled Rice By Instrumental and Sensory Methods - Perez, Consuelo M.; Juliano, Bienvenido O.; BOURNE, MALCOLM C.; ANZALDÚA-MORALES, ANTONIO (Wiley, 1993)
Fifteen milled rice varieties covering the usual range of amylose content and cooked rice hardness were used in a collaborative study to verify the sensitivity of the present objective method for measuring cooked rice hardness. The grains were cooked either in a rice cooker using a fixed water:rice ratio of 2:1, or by boiling in excess water for the predetermined optimum cooking time for each sample followed by draining. Hardness of cooked rice was measured in an Instron Universal Testing Machine (UTM) using two methods: (1) puncture of 100 individual grains and (2) extrusion through a 30 cm2 Ottawa Texture Measuring System (OTMS) cell with either a 3.2‐ or 4.8‐mm‐diam. holes plate. Hardness values were compared with sensory scores by a trained panel composed of 11 members. Sensory hardness of the rices cooked in a fixed amount of water showed very good correlation with puncture force (r = 0.94, P < 0.01) and with extrusion force through a 3.2‐mm‐diam. holes plate (r = 0.94). The correlation coefficient between puncture force and extrusion force was 0.97. Paired comparison test by the sensory panel on three pairs of rices verified consumers’ claims with respect to preference between members of each pair and agreed with results of ranking test.